ASSESSING USER EXPERIENCE OF SITURAWA GEDE TOURISM WEBSITE USING PSSUQ AND HEURISTIC - Anie Yoraeni; Cep Adiwiharja; Syifa Nur Rakhmah; Sinta Rukiandari; Sari Hartini (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2026)
The Siturawagede platform is an information site built to support services, promotions, and interactions with the public. Therefore, the quality of the user experience (UX) is a crucial factor in ensuring the site's effective, efficient, and satisfying use. This study aims to analyze the user experience of the Siturawagede website, measure user satisfaction with ease of use, efficiency, and information quality using the Post-Study System Usability Questionnaire (PSSUQ), assess the site's compliance with Nielsen's usability principles through a heuristic evaluation, and provide recommendations for improving the site's user-friendliness. The study involved 100 respondents who completed the PSSUQ questionnaire and three expert evaluators who conducted the heuristic assessment. The results showed that the average PSSUQ score of 2.6 was categorized as "good." This is based on the PSSUQ 1–7 scale, where a score closer to 1 indicates a positive experience (Strongly Agree) and a score closer to 7 indicates a negative experience (Strongly Disagree), indicating that users were quite satisfied with the system. The heuristic evaluation obtained a score of 1.49, identifying several minor navigation issues, but the system was generally good and needed only minor improvements. These findings provide guidance for improving the quality of the Siturawagede website to make it more informative and optimal in supporting tourism management.